2009
DOI: 10.1038/emboj.2009.117
|View full text |Cite
|
Sign up to set email alerts
|

XBP-1 regulates signal transduction, transcription factors and bone marrow colonization in B cells

Abstract: XBP-1, a transcription factor that drives the unfolded protein response (UPR), is activated in B cells when they differentiate to plasma cells. Here, we show that in the B cells, whose capacity to secrete IgM has been eliminated, XBP-1 is induced normally on induction of differentiation, suggesting that activation of XBP-1 in B cells is a differentiation-dependent event, but not the result of a UPR caused by the abundant synthesis of secreted IgM. Without XBP-1, B cells fail to signal effectively through the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
169
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(186 citation statements)
references
References 39 publications
12
169
5
Order By: Relevance
“…By stabilizing the dimer, an increase in the acyl chain saturation could lower the threshold of luminal stress required for unfolded protein-dependent activation of IRE1α and PERK, and levels of unfolded protein stress could modulate the response to lipids by a similar cooperative mechanism. Lipid sensing by IRE1 and PERK may account for instances, such as B-cell development, marked by an apparent discrepancy between a modest level of unfolded protein load and substantial UPR signaling (33)(34)(35). It may therefore be interesting to examine the potential role of lipids as instigators of what has been termed an anticipatory UPR (36, 37).…”
Section: Discussionmentioning
confidence: 99%
“…By stabilizing the dimer, an increase in the acyl chain saturation could lower the threshold of luminal stress required for unfolded protein-dependent activation of IRE1α and PERK, and levels of unfolded protein stress could modulate the response to lipids by a similar cooperative mechanism. Lipid sensing by IRE1 and PERK may account for instances, such as B-cell development, marked by an apparent discrepancy between a modest level of unfolded protein load and substantial UPR signaling (33)(34)(35). It may therefore be interesting to examine the potential role of lipids as instigators of what has been termed an anticipatory UPR (36, 37).…”
Section: Discussionmentioning
confidence: 99%
“…44 Moreover, PC survival factors are directly induced by XBP-1s including IL-6 37 and iNOS, 45 and nitric oxide (NO), the byproduct of iNOS activity, has also been described to have anti-apoptotic effects in different cell subsets. 46,47 Recently, it was shown that iNOS deficiency in PC leads to a decrease in both viability and an increase in caspase 3 activation, under conditions of polyclonal B cell stimulation in vitro and in vivo.…”
Section: Plasma Cell-intrinsic Mechanisms Of Survivalmentioning
confidence: 99%
“…52 PC migrate to the BM by up-regulating CXCR4 in order to respond to CXCL12 which is expressed in the medullary cords of LN and in the BM. 53 Interestingly, XBP-1 has been implicated in PC migration toward CXCL12, 44 suggesting that acquisition of CXCL12 responsiveness through the chemokine receptor CXCR4 is part of the PC differentiation program. Within the BM niche itself, particular cytokines are very important for sustaining PC survival.…”
Section: Plasma Cell-intrinsic Mechanisms Of Survivalmentioning
confidence: 99%
“…Master regulators such as Blimp-1 or IFN regulatory factor 4 (IRF4) belong to this latter group and are responsible for repressing transcription of B cell genes or actively promoting the expression of ASC genes, respectively (4-9). X-box binding protein 1 (XBP-1) is a transcription factor also implicated in plasma cell differentiation, although its mechanism of action is less well defined (10)(11)(12)(13). XBP-1 has a role in the unfolded protein response (UPR) that is induced when the endoplasmic reticulum (ER) is overloaded with unfolded proteins (14,15).…”
mentioning
confidence: 99%
“…It is thus not surprising that defective expression of XBP-1 impacts on the normal operation of a plasma cell. The role of XBP-1 in the development of plasma cells is, however, proposed to extend beyond its function in the UPR (10,20). Although XBP-1 is expressed at a low level throughout B cell development, expression is induced dramatically during plasma cell differentiation in response to cytokines such as IL-4 (11).…”
mentioning
confidence: 99%